Vortex Solutions in the Presence of Dark Portals - Venegas-M, H; Arias-Reyes, P; Vargas-Arancibia, D (World Scientific, 2022)
The existence of hidden sectors weakly coupled to the visible one has been extensively studied as a way to extend the Standard Model (SM) and to provide a good dark matter candidate. In this work we analyze two models in which gauge and scalar hidden fields interact with the visible sector which, for simplicity we take as an Abelian-Higgs model. In one of them, the hidden sector consists of an uncharged scalar. The connection with the visible Abelian-Higgs sector is in this case provided by the interaction between the scalars in the two sectors and also by the coupling between the hidden scalar and the visible squared field strength. This model can be seen as an extension of previously studied ones both in high energy and in condensed matter physics and the solutions that we find indicate that it could be relevant in connection to establishing the dark matter relic density. In the second model, both sectors correspond to spontaneously broken gauge theories and hence they feature classical vortex solutions. By introducing three different portals between the two sectors, we analyze the dependence of the model dynamics on the portal parameters and discuss the physical implications in connection with dark matter and gravitational radiation issues. © 2022 World Scientific Publishing Company.